'Defoliating the World': Ecocide, Visual Evidence and 'Earthly Memory'. Issue 2 (4th May 2018) - Meszaros Martin, Hannah
Abstract: This article poses the US-led War on Drugs as an ecocidal force, whereby certain species and ecosystems are extinguished in the name of the 'greater good'. In this never-ending war, environmental violence is intertwined with political violence; when nonhuman lives, including those of plants, become subject to eradication, a co-criminalisation occurs as natural ecosystems and human life cannot be separated. I examine how these forms of violence are depicted and the implications for visual evidence, forensics and legal forums in the context of the aerial fumigation of the coca plant in Colombia. The text traverses a series of frames of representation, each operating through different media and at different scales, in order to unfold the complex relationship between violence, law and the visible. What would it mean to broaden our terms of violence to include nonhuman subjects, and actions such as defoliation? I argue for new forms of evidentiary truth that might facilitate a reorientation of political and juridical forums to include 'earthly memory'.